The Aryl Hydrocarbon Receptor (AhR) Level Based on Age and Clinical Type of Melasma - Danil, Rezkyana; Jusuf, Nelva Karmila; Putra, Imam Budi (CoinReads Media Prima, 2024)
Introduction: Melasma is the most common pigmentation condition on the face due to excessive melanin production and release. The main predisposing factor for melasma is UV exposure. Aryl Hydrocarbon Receptor (AhR) is a ligand-dependent transcription factor that regulates the expression of a very large number of target genes in humans. Facial hyperpigmentation is increased in people living in air-polluted areas with particulate matter2.5 (PM2.5) concentrations. Dioxin compounds contained in PM2.5 can activate AhR signaling. This study aims to determine the aryl hydrocarbon receptor (AhR) level based on age and clinical type of melasma. Methods: This study was an observational study with a cross-sectional design of 30 women with melasma at Prof. CPL Hospital. This study was conducted after obtaining ethical clearance from the Research Ethics Commission of the University of North Sumatra and has obtained permission from the research field of Prof. Chairuddin Panusunan Lubis Hospital. All subjects underwent history taking, physical examination, dermatological examination, and blood sampling to assess AhR levels by ELISA test. Data were analyzed with Chi square test to assess AhR levels based on age, and to assess AhR levels based on clinical type of melasma with Kruskal Wallis test. Results: This study shows that the majority of melasma age is 41-50 years with the highest mean AhR level is 882,61 ng/mL, while the lowest AhR level is in the age range of 20-30 years with a mean of 271,5 ng/mL. Chi square test showed that there was a significant relationship between AhR levels and age (p < 0,001). The highest mean AhR levels in melasma subjects were centrofacial type with a mean of 795,50 ng/mL, while the lowest mean AhR levels were found in melasma subjects with malar type with a mean of 623,36 ng/mL. The Kruskal Wallis test showed that there was no significant difference in AhR levels based on the clinical type of melasma (p = 0,930). Conclusion: That increased the age, the highest AhR levels. The highest average AhR level was centrofacial type of melasma. There was no significant difference in AhR levels based on the clinical type of melasma.